2004
DOI: 10.1073/pnas.0402525101
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and symmetry presculpt the free-energy landscape of proteins

Abstract: We present a simple physical model that demonstrates that the native-state folds of proteins can emerge on the basis of considerations of geometry and symmetry. We show that the inherent anisotropy of a chain molecule, the geometrical and energetic constraints placed by the hydrogen bonds and sterics, and hydrophobicity are sufficient to yield a free-energy landscape with broad minima even for a homopolymer. These minima correspond to marginally compact structures comprising the menu of folds that proteins cho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
268
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(284 citation statements)
references
References 44 publications
15
268
1
Order By: Relevance
“…Previous studies have shown that the large number of common attributes of globular proteins reflect a deeper underlying unity in their behavior (1,2,31). At odds with conventional belief, a consequence of our hypothesis is that the gross features of the energy landscape of proteins result from the amino acid aspecific common features of all proteins.…”
Section: Resultscontrasting
confidence: 55%
“…Previous studies have shown that the large number of common attributes of globular proteins reflect a deeper underlying unity in their behavior (1,2,31). At odds with conventional belief, a consequence of our hypothesis is that the gross features of the energy landscape of proteins result from the amino acid aspecific common features of all proteins.…”
Section: Resultscontrasting
confidence: 55%
“…Proteins are highly compact under folding conditions, with an average packing density resembling that of small organic solids (58). It has been shown that the conformational freedom of a compactly folded tube of polypeptide chain dimensions is severely limited by excluded volume restrictions in the marginally compact phase (47,59). Such chain organization is an automatic consequence of compact geometry and does not result in a glassy landscape.…”
Section: Universality Implies a Backbone-basedmentioning
confidence: 99%
“…Accordingly, it can be concluded that the free energy landscape is presculpted (47,48) into a few thousand intrinsically stable domains which are unmasked upon switching from unfolding to folding conditions. Specific sequences would be needed to discriminate among the possibilities in this repertoire, and exactly how this happens remains to be explained.…”
Section: Part 2 Questioning the Current Perspective: A Tale Of Two Lmentioning
confidence: 99%
“…An alternative scheme would assume a single (or few) conformational property to be directly encoded in sequences, resulting in a small number of sequence-dependent parameters, whereas other conformational features would arise from sequence-independent constraints. The importance of such constraints has been recently emphasized by Banavar and collaborators (11).…”
mentioning
confidence: 99%